Delivering an Integrated Adolescent Multi-Agency Specialist Service to Families with Adolescents at Risk of Care: Outcomes and Learning from the First Ten Years. (25th February 2020) - Talbot, Laura; Fuggle, Peter; Foyston, Zoe; Lawson, Kim
Abstract: This article presents a ten-year service evaluation of the Adolescent Multi-Agency Specialist Service (AMASS), an edge of care service based within Islington Children's Services. A description of the AMASS model and the social care and mental health outcomes for the cohort of families supported by the service across this period ( n  = 181) are presented. The service had a completion rate of 85 per cent and improvements in both social care and mental health outcomes were found for a significant proportion of those who completed the intervention. Placement stabilisation was achieved for 82 per cent of young people across the service's three referral categories (home stability, foster placement stability and return home from care). Statistically significant reductions in parental report scores were found on the Strengths and Difficulties Questionnaire and two measures of family functioning in a paired sample ( n  = 48). Potential learning arising from the AMASS model, in terms of implications for service design for adolescent edge of care interventions, and the limitations of this service evaluation are discussed.